2020
DOI: 10.1186/s13071-020-3924-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for family-level variation of phenotypic traits in response to temperature of Brazilian Nyssorhynchus darlingi

Abstract: Background: Nyssorhynchus darlingi (also known as Anopheles darlingi) is the primary malaria vector in the Amazon River Basin. In Brazil, analysis of single nucleotide polymorphisms (SNPs) previously detected three major population clusters, and a common garden experiment in a laboratory setting revealed significant population variation in life history traits. Increasing temperatures and local level variation can affect life history traits, i.e. adult longevity, that alter vectorial capacity with implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…darlingi is related to its behavioural characteristics, susceptibility to human malaria parasites and adaptation. It was found that this species has genetic and even phenotypic variations within the same population and between different populations, mainly due to climatic (seasonal variation) and environmental factors (degradation of the environment and geographical barriers such as biomes) 32,33 . These issues are of concern for public health because the vector can maintain transmission in different regions in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…darlingi is related to its behavioural characteristics, susceptibility to human malaria parasites and adaptation. It was found that this species has genetic and even phenotypic variations within the same population and between different populations, mainly due to climatic (seasonal variation) and environmental factors (degradation of the environment and geographical barriers such as biomes) 32,33 . These issues are of concern for public health because the vector can maintain transmission in different regions in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…(40,41,42) At a molecular level, several markers showed diversity among populations along with geographic variation, such as ITS2 in rDNA, (43) cytochrome oxidase I gene (COI) in mtDNA, (44,45) microsatellites (46)(47)(48)(49)(50)(51) and single nucleotide polymorphisms (SNPs). (4,52,53) Despite these multiple behavioural, morphological, and genetic distinctions, some studies claim that these differences are divergences among populations, not enough to evidence An. darlingi as a complex of cryptic species.…”
mentioning
confidence: 99%